TO COMPARE THE EFFECTS OF SPRINT AND PLYOMETRIC TRAINING PROGRAM ON ANAEROBIC POWER AND AGILITY IN COLLEGIATE MALE FOOTBALL PLAYERS (International Journal of Physiotherapy, 2015)
Background: Football is the world’s most popular game and is played by men, women and children of all ages and levels of ability. Success as a player requires an appropriate mixture of mental, physical, technical and tactical ability. Many decisive moments are defined by anaerobic activities such as sprinting, jumping & contests for the football. Agility is an ability of the neuromuscular system to coordinate explosive changes of direction of an individual and/or multiple body segments in all planes of motion. Plyometric Training has been advocated for sports that require the athletes to have explosive power and agility. Similarly previous sprint training studies have shown improvement in the dynamic athletic lower body performance. Advanced technique such as plyometric training protocol has proven more effective but not much studies have been done to assess its effectiveness over Plyometric Training, namely Lower Body Power and AgilityMethods: A total of 30 collegiate football players were taken with a mean age of 21.5 with a standard deviation of one. They were randomized into two groups (Group A – Sprint Training & Group B – Plyometric Training). Each group consist of 15 players were selected based on their selection criteria. Informed consent was obtained from the subjects. The study was conducted for six weeks (12 sessions) with both the Groups. Evolution parameters are vertical jump height, 40 yard dash, illinois agility Test.Results: Independent t test was used to analysis data. On comparing VJH, Plyometric Training shows (49.26) which have the higher mean value is more effective than Sprint Training (44.93).On comparing Anaerobic power Plyometric Training shows (4150.8) which has the higher Mean value is more effective than Sprint Training (3782.4), on comparing 40 yard dash Plyometric Training shows (5.335) which has the lower Mean value is more effective than Sprint Training (5.490). Illinois Agility Test Plyometric Training shows (15.38) which have the lower mean value is more effective than Sprint Training (16.80).Conclusion: Superiority of Plyometric Training Group over Sprint Training Group is particularly evident for improvements in Anaerobic Power and Agility. These results suggest that Plyometric Training is advantageous for developing lower body Explosive Power and Agility. Explosive activities are required in many sports and physical activities; coaches and participants should therefore consider a Plyometrics training program that incorporates specific exercises according to the needs of individual’s athletic performance as part of the overall training program.